2015
DOI: 10.5301/tj.5000237
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Levels of E-cadherin and MMP-13 in Prostate Cancer Patients: Correlation with PSA, Testosterone and Pathological Parameters

Abstract: The results suggest that these parameters could be used both in the diagnosis and prognosis of prostate cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…In colorectal patients, Velikova et al 33 determined that there was no statistically significant difference between sE-cadherin levels between controls and patients. However, Bonaldi et al 17 suggested that sE-cadherin was lower in patients with prostate cancer compared to controls. Several studies concluded that decreased expression of E-cadherin facilitated tumor invasion and metastasis in various tumors such as ovarian, endometrial and cervical cancers.…”
Section: Turan Et Al Vitronectin Se-cadherin and Tgf-β1 Levels In Ementioning
confidence: 99%
See 1 more Smart Citation
“…In colorectal patients, Velikova et al 33 determined that there was no statistically significant difference between sE-cadherin levels between controls and patients. However, Bonaldi et al 17 suggested that sE-cadherin was lower in patients with prostate cancer compared to controls. Several studies concluded that decreased expression of E-cadherin facilitated tumor invasion and metastasis in various tumors such as ovarian, endometrial and cervical cancers.…”
Section: Turan Et Al Vitronectin Se-cadherin and Tgf-β1 Levels In Ementioning
confidence: 99%
“…15 But, there are conflicting results about soluble E-cadherin (sE-cadherin) levels in cancer. Some suggest that serum sE-cadherin levels were higher, 16 while others were revealed that sE-cadherin levels were significantly lower 17 in patients compared to controls.…”
Section: Introductionmentioning
confidence: 99%
“…The loss of this adhesion molecule is accompanied by increases in other mesenchymal markers such as N-cadherin, vimentin and fibronectin [51]. An increasing number of studies demonstrate that in many tumours including prostate, loss of E-cadherin increases tumour cell motility and invasiveness and is associated with poor prognosis in cancer patients [39,[52][53][54]. Similarly, examination of prostate cancer tissue samples using immunohistochemistry also revealed a reduction in the expression of cellular membrane E-cadherin that was concomitant with increasing Gleason score, clinical stage and a decline in survival [55].…”
Section: Emt and Prostate Cancer Progressionmentioning
confidence: 99%
“…In the clinical setting, plasma concentrations of E-cadherin are low in the later stage of prostate cancer patients and correlate with raised levels of PSA. In keeping with this, the use of plasma E-cadherin concentrations as a biomarker of the metastatic potential and to predict prognosis of prostate cancer has been proposed in clinical practice along with the use of PSA, particularly when aberrant modification of E-cadherin is likely to be involved in cancer invasion [53]. In addition to this, in vivo and in vitro studies have found that inhibition of N-cadherin using antibodies is able to delay the progression of prostate cancer to castration resistance and also to inhibit the invasion and metastasis of castrationresistant tumour growth suggesting the fundamental role of N-cadherin in promoting castration resistance and metastasis [56].…”
Section: Emt and Prostate Cancer Progressionmentioning
confidence: 99%
“…The plasma concentration of MMP13 can have a diagnostic role in a prostatic carcinoma patient. (10,11) The expression of several MMPs and TIMPs in prostatic carcinoma like MMP 2, 7, 9, 13 and 4 and TIMP 1 and 2 have recently been reported (7,12,13) and shows that overexpression of MMPs induces tumour growth. (14,15) The proteins encoded by TIMP gene family are natural inhibitors of matrix metalloproteinases.…”
mentioning
confidence: 99%